Poly(2-oxazoline)s based biomaterials: A comprehensive and critical update. (September 2018) - Lorson, Thomas; Lübtow, Michael M.; Wegener, Erik; Haider, Malik S.; Borova, Solomiia; Nahm, Daniel; Jordan, Rainer; Sokolski-Papkov, Marina; Kabanov, Alexander V.; Luxenhofer, Robert
Abstract: Poly(2-oxazoline)s have been investigated for decades as biomaterials. Pioneering early work suggested that hydrophilic poly(2-oxazoline)s are comparable to poly(ethylene glycol) regarding their potential as biomaterials, but the ready commercial availability of the latter has led to its meteoric rise to become the gold standard of hydrophilic synthetic biomaterials. In contrast, poly(2-oxazoline)s almost fell into oblivion. However, in the last decade, this family of polymers has gained much more interest in general and as biomaterials in particular. The rich chemistry and comparably straightforward synthesis of poly(2-oxazoline)s gives many opportunities for tailoring the properties of the resulting biomaterials, allowing the chemist to explore new conjugation chemistry, and to fine-tune the molar mass, hydrophilic-lipophilic balance as well as architecture. Thus, the wide range of demands for various applications of biomaterials can be suitably addressed. This review aims to give a comprehensive and critical update of the development of poly(2-oxazoline) based biomaterials, focusing on the last 5 years, which have seen an explosive increase of interest. We believe that the research regarding this diverse family of polymers will remain strong and will keep growing, in particular after the promising first-in-human studies of a poly(2-oxazoline) drug conjugate. This review aims at researchers and students new to this polymer family and seasoned poly(2-oxazoline) experts alike and attempts to showcase how the chemical diversity of poly(2-oxazoline)s allows a relatively facile and broad access to biomaterials of all kinds.